Dividing neutrophils in subsets reveals a significant role for activated neutrophils in the development of airway hyperreactivity. Issue 3 (13th December 2018) - Ekstedt, Sandra; Säfholm, Jesper; Georén, Susanna Kumlien; Cardell, Lars Olaf
Abstract: Background: Previous research has emphasized the importance of eosinophils in allergic asthma, while paying less attention to neutrophils. The known functionality of neutrophils in the inflammatory process has recently changed and knowledge about subsets of neutrophils, as characterized by their expression of CD16 and CD62L, has surfaced. Their specific roles in asthma are still unknown. Objective: To study the functional differences between subsets of neutrophils by characterizing the impact of individual subsets on airway smooth muscle reactivity. Methods: The direct effect of neutrophils on airway hyperresponsiveness was assessed by co‐culturing different subsets of neutrophils (produced by LPS in vitro stimulation) with human isolated small airways or murine tracheae with subsequent evaluation of smooth muscle reactivity to bradykinin in myographs. Supernatants and tissue were saved for ELISA and immunohistochemistry. Results: The CD16 high CD62L dim neutrophils were found to enhance the response to bradykinin in both human isolated small airways and murine tracheae. No such effects were obtained for the other subsets. The response is due to an upregulation of bradykinin receptor 2 through release of TNFα from the neutrophil. Conclusions and Clinical Relevance: The present study introduces a new concept regarding the role of neutrophils and defines a novel direct link between a specific activated neutrophil subset and airway smooth muscle, establishing neutrophils as important players in the development of asthmatic airway hyperactivity.